Clinical value of stool culture in paediatric oncology patients: hospital evaluation and UK survey of practice. Issue 1 (January 2017) - O'Connor, O.; Cooke, R.P.D.; Cunliffe, N.A.; Pizer, B.
Summary: Diarrhoea is a frequently occurring symptom in paediatric oncology patients. The role of routine testing for enteric bacteria in hospitalized patients with diarrhoea is considered limited, but the diagnostic value of testing in children with oncological conditions has not been reported. Therefore, we conducted a five-year retrospective service evaluation in our tertiary paediatric oncology unit together with a national survey of 21 centres to estimate the utility of stool cultures in oncology patients with diarrhoea and the national approach to testing. Our local survey demonstrated very low diagnostic yield using routine enteric stool cultures with only one sample out of 842 (0.1%) testing positive. The national survey demonstrated considerable variation in practice. There is little evidence to support the use of conventional stool culture for enteric bacteria in children with cancer in our centre. These findings should inform national testing policies.